Changes in performance and thermal stability of Ni0.8Co0.1Al0.1/graphite batteries with excessive water - Xi Liu; Jingbo Mao; Hongtao Yan; Chunjing Lin; Chuang Qi; Tao Yan; Li Lao; Yazhou Sun (IET Energy Systems Integration)
Abstract During the production process of lithium‐ion batteries, there exists a scenario of excessive water inside the battery due to poor water control in the factory environment. In addition, the battery housing may be damaged by corrosion, external vibration etc., which would cause water to enter the battery. To the best of the authors’ knowledge, there is little literature to reveal the influencing mechanism related to the above issue. The effects of excessive water on battery performance and safety were discussed. The results show that when the battery absorbs excessive water, the capacity decreases and the self‐discharging rate increases rapidly. The self‐heating temperature of the battery shows an increasing trend. The thermal runaway temperature decreases significantly with the time from self‐heating to thermal runaway dramatically shortened. The thermal stability of the battery deteriorates throughout the reaction process. This is mainly due to the mechanisms by which the water absorbed in the battery reacts with the electrolyte and the electrode material, resulting in the decrease of the electrolyte conductivity and the corrosion of the electrode material, as well as the thickening of the Solid Electrolyte Interface film and the accumulation of impurities. The findings are of positive significance in demonstrating the quantitative relationship between excessive water and the performance and safety of batteries. Also, it can add to the understanding of the complex scenarios of battery spontaneous failure, which is vital for solving battery self‐thermal runaways.